DECENTRALIZED BUSINESS IN THE BLOCKCHAIN ERA: MAPPING RESEARCH TRENDS AND IDENTIFYING FUTURE RESEARCH DIRECTIONS - Fadly Alan Nur Datumula (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The evolution of decentralized business models (DBMs) has fundamentally transformed the global economic landscape, shifting from its initial cryptocurrency-centric origins to a wide array of diverse industrial applications. This study aims to comprehensively map emerging research trends and identify critical knowledge gaps in the field of decentralized business during the current blockchain era. Employing a rigorous Systematic Literature Review (SLR) and bibliometric analysis through the PRISMA framework, a total of 142 eligible documents retrieved from the Scopus database (covering the period 2017–2023) were meticulously analyzed. The findings reveal three distinct evolutionary phases: the initiation phase (2017–2018), stable development (2019–2021), and a recent period of rapid acceleration (2022–2023). Detailed keyword clustering identifies Decentralized Finance (DeFi), Smart Contracts, and Decentralized Autonomous Organizations (DAOs) as the dominant thematic pillars of current academic discourse. Geographically, a